Sinergi Antara Ilmu Medis dan Fiqih Dalam Penggunaan Air Doa Untuk Penyembuhan di Sumedang Utara - Nurulaeni, Devia; Rifdah, Nur Rahidah Hana; Maolida, Nurul; Karlina, Silvi; Hidayat, Taufik; Supriyadi, Tedi; Faozi, Akhmad (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to analyze ulama perspectives on prayer water use based on fiqh studies and Thibbun Nabawi, explore medical personnel views on prayer water potential as complementary therapy, and identify convergence points between religious and medical approaches in using prayer water for healing. The study employed a qualitative approach with exploratory study design. Findings show significant convergence between religious and medical perspectives. Ulama provide theological foundation through QS Al-Anbiya verse 30 and Thibbun Nabawi practices, positioning prayer water as wasilah in seeking healing efforts. Medical personnel acknowledge placebo effects and psychological dimensions of prayer water through psychoneuroimmunology mechanisms. Both perspectives agree that belief and positive suggestion play important roles in healing, with prayer water functioning as complementary therapy that does not replace primary medical treatment. This integration opens opportunities for developing holistic healthcare models that accommodate spiritual values without neglecting evidence-based medicine principles.